2021
DOI: 10.21203/rs.3.rs-957306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility Pattern of Urinary Tract Infection among Pregnant Women Attending Hargeisa Group Hospital, Hargeisa, Somaliland

Abstract: The aim of this study was to determine the prevalence, antimicrobial susceptibility pattern and associated factors of urinary tract infection (UTI) among pregnant women attending Hargeisa Group Hospital (HGH), Hargeisa, Somaliland. A cross-sectional study was conducted at HGH, Hargeisa, Somaliland and participants were selected by systematic random sampling technique. Clean catch midstream urine samples were collected from 422 participants and cultured and antimicrobial susceptibility pattern was determined fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The most common gram-negative bacteria isolated from samples in our investigation was E. coli (55.0%). These findings are consistent with those of several other published studies where the prevalence of E. coli was 97.0, 92.6, 74.0, 55.0, 49.3, 43.5, 41.9, and 40.0% (Arora et al, 2016;Odoki et al, 2019;Chen et al, 2020;Daoud et al, 2020;Ali et al, 2022;Huang et al, 2022;Jagadeesan et al, 2022;Komagamine et al, 2022). In our study, 10.3389/fmicb.2022.965053…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The most common gram-negative bacteria isolated from samples in our investigation was E. coli (55.0%). These findings are consistent with those of several other published studies where the prevalence of E. coli was 97.0, 92.6, 74.0, 55.0, 49.3, 43.5, 41.9, and 40.0% (Arora et al, 2016;Odoki et al, 2019;Chen et al, 2020;Daoud et al, 2020;Ali et al, 2022;Huang et al, 2022;Jagadeesan et al, 2022;Komagamine et al, 2022). In our study, 10.3389/fmicb.2022.965053…”
Section: Discussionsupporting
confidence: 94%
“…In our study, 96.0% of the pathogens were MDR, compared to 91.3% in Nepal, 85.5% in Somaliland, 83.0% in Haryana, 45.1% in Tunisia, and 42.6% in China (Ben Ayed et al, 2019;Huang et al, 2022;Malik et al, 2021;Shilpakar et al, 2021;Ali et al, 2022). The inappropriate and indiscriminate use of broad-spectrum antibiotics and prolonged hospital stay are key etiological factors associated with MDR infections (Prestinaci et al, 2015).…”
Section: Discussionmentioning
confidence: 58%
“…The results of this study demonstrated antibiotic resistance to ceftriaxone (73.68%). These results are similar to those posted earlier by Ali et al 2022. On the other hand, the results disagree with those results previously published by Johnson et al, 2021.…”
Section: Anthropometric Resultssupporting
confidence: 66%
“…Twenty studies [19], [20], [34], [43], [21], [22], [24], [25], [27]- [29], [33][30] [31][15], [16], [32], [36], [37], [42] reported the mean age of their study subjects. The lowest mean age was 6 years reported by Fenta et al [27] while the highest mean age was 39 years reported in the study by Nigusse et al [37].…”
Section: Agementioning
confidence: 99%
“…Twelve studies [21][24] [27][28] [29][18], [33], [34][37] [32], [41][15] investigated residence as a factor for urinary tract infections. None of the above studies found signi cant association between residence and occurrence of UTIs.…”
Section: Residencementioning
confidence: 99%